Analisis Business Process Management Notation (Pembelian Barang) pada UMKM : Studi Kasus - Azaro, Khoirin; Ekasari, Kurnia; Indrawan, Andi (Journal of Industrial Engineering & Management Research, 2021)
This is the field of study that deal with business process management. This turns out to be problematic because to get successful business need appropriate business process management. The way to describe a business process is making a business process modeling notation (BPMN). BPMN make business process easier to understand for all users in the organization. Small and medium enterprise (SME) also needs to designed BPMN to achieve business effectiveness. This study use qualitative approach, data collected from interview and observation in Swamart Swalayan as small retail enterprise. The overall goal of this work was to find out the evaluation purchase order system and existing supplies at Swamart Supermarkets by using BPMN. From the result, Swamart Supermarket have some problem in handling the inventory. Improvement of inventory management and duties segregation are needed by Swamart Swalayan to achieve better goals.